2021
DOI: 10.1186/s13643-021-01733-2
|View full text |Cite
|
Sign up to set email alerts
|

Dealing with predatory journal articles captured in systematic reviews

Abstract: Background Systematic reviews appraise and synthesize the results from a body of literature. In healthcare, systematic reviews are also used to develop clinical practice guidelines. An increasingly common concern among systematic reviews is that they may unknowingly capture studies published in “predatory” journals and that these studies will be included in summary estimates and impact results, guidelines, and ultimately, clinical care. Findings Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 15 publications
1
32
0
1
Order By: Relevance
“…Furthermore, the methodological research conducted by Fleming et al ( Fleming et al, 2014 ), reported that among 372 interventional systematic reviews, those published in clinical journals with higher IF appeared to have better methodological quality based on the AMSTAR tool. In general, rigorous peer-review and publication processes can improve the quality of publications ( Rice et al, 2021 ), and high-IF journals frequently adhere to the above processes. The research with funds support often needs to be strictly reviewed and assessed by their funders, which may potentially affect the methodological quality of MAs included in this systematic investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the methodological research conducted by Fleming et al ( Fleming et al, 2014 ), reported that among 372 interventional systematic reviews, those published in clinical journals with higher IF appeared to have better methodological quality based on the AMSTAR tool. In general, rigorous peer-review and publication processes can improve the quality of publications ( Rice et al, 2021 ), and high-IF journals frequently adhere to the above processes. The research with funds support often needs to be strictly reviewed and assessed by their funders, which may potentially affect the methodological quality of MAs included in this systematic investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Articles considered to be from predatory journals or with commercial funding related to BMS will be marked in the data charting and analysis will be carried out both with and without those articles included. The presence of predatory articles and funding sources will be discussed where relevant [53].…”
Section: Step 4: Chart the Datamentioning
confidence: 99%
“…[12][13][14] Unfortunately, there are presently no standardized methods or guidelines for the exclusion of information from predatory journals, although some ideas are emerging. 14,15 In the meantime, authors, reviewers, and readers should remain vigilant for unreliable information in systematic reviews and meta-analyses.…”
mentioning
confidence: 99%
“…11 Information from predatory journals is also now being increasingly captured in systematic reviews, and has the potential to warp their results and influence their conclusions. [12][13][14] Unfortunately, there are presently no standardized methods or guidelines for the exclusion of information from predatory journals, although some ideas are emerging. 14,15 In the meantime, authors, reviewers, and readers should remain vigilant for unreliable information in systematic reviews and meta-analyses.…”
mentioning
confidence: 99%